IntelliCage: the development and perspectives of a mouse- and user-friendly automated behavioral test system - Lipp, Hans-Peter; Krackow, Sven; Turkes, Emir; Benner, Seico; Endo, Toshihiro; Russig, Holger (Frontiers in Behavioral Neuroscience, 2024)
IntelliCage (IC) for mice is an industrialized home cage system equipped with four corner structures harboring symmetrical double panels for operant conditioning at each of the two sides, either by reward (access to water) or by aversion (air puff, LED light). Corner visits, nose-pokes and actual licks at bottle-nipples are recorded individually using subcutaneously implanted transponders for RFID identification of up to 16 same-sex adult mice. This allows for recording individual in-cage activity of mice and applying reward/punishment operant conditioning schemes in corners using workflows designed on a convenient graphic user interface. IC development had four roots: (i) dissatisfaction with standard approaches for analyzing mouse behavior, including standardization and reproducibility issues, (ii) dismissal of ethical guidelines by housing and handling, (iii) the increasing number of mouse models had produced a high work burden on classic manual behavioral phenotyping of single mice. and (iv), studies of transponder-chipped mice in outdoor settings revealed clear genetic behavioral differences in mouse models corresponding to those observed by classic testing in the laboratory. The latter observations were important for the development of home-cage testing in social groups, because they contradicted the traditional belief that to prevent disturbance by other group members animals must be tested under social isolation. The use of the IC reduced indeed the amount of classic testing remarkably, while its flexibility was proved in a wide range of applications worldwide including transcontinental parallel testing. Essentially, two lines of testing emerged: sophisticated analysis of spontaneous behavior in the IC for screening of new genetic models, and hypothesis testing in many fields of behavioral neuroscience. Upcoming developments of the IC aim at improved stimulus presentation in the learning corners and videotracking of social interactions within the IC. The main advantages of the IC are (i) that mice live in social context and are not stressfully handled for experiments, (ii) that studies are not restricted in time and can run in absence of humans, (iii) that it increases reproducibility of behavioral phenotyping worldwide, and (iv) that the industrial standardization of the cage permits retrospective data analysis with new statistical tools even after many years.